A Multidisciplinary Approach for the Mapping, Automatic Detection and Morphometric Analysis of Ancient Submerged Coastal Installations: The Case Study of the Ancient Aegina Harbour Complex - Nikos Georgiou (MDPI AG, 2021)
The documentation of underwater cultural heritage (UCH) is the basis for sustainable maritime development including its protection, preservation, and incorporation in coastal zone management plans. In this study, we present a multidisciplinary, non-intrusive downscale approach for the documentation of UCH implemented on the coastal area of Aegina Island, Greece, where a unique submerged harbour complex is preserved. This approach succeeded in obtaining information that serves both geomorphological and archaeological purposes in a time- and cost-effective way, while obtaining information of centimeters to millimeters scale. The geomorphology of the area was mapped in detail through marine geophysical means while ancient submerged conical rubble structures and breakwaters were documented using automatic seafloor segmentation techniques, revealing previously unknown sites of archaeological interest. The structures’ parameters were extracted from the acoustic data to analyze their morphometry, while photogrammetry was realized using a Remotely Operated Vehicle to expose their micro-structure. The spatial distribution of the structures revealed the construction of a well-planned harbour complex with multiple passages and different possible functionalities. Finally, through the structures’ morphometric analysis (geometry and terrain statistical parameters) their preservation status was revealed, demonstrating the anthropogenic impact on the submerged ancient structures due to the modern harbor activity.